Communicating Effectively About Organ Donation: A Randomized Trial of a Behavioral Communication Intervention to Improve Discussions About Donation. Issue 2 (March 2015) - Siminoff, Laura A.; Traino, Heather M.; Genderson, Maureen Wilson
Abstract : Background: Families' refusal to authorize solid organ donation contributes to the organ deficit in the United States. The importance of communication to reducing refusal to requests for solid organ donation at the bedside and thus increasing the supply of transplantable organs cannot be overstated. This research compares 2 versions of an innovative communication skills training program for organ procurement organization request staff, Communicating Effectively About Donation (CEaD), designed to improve the quantity and quality of organ donation discussions with family decision makers of deceased patients. Methods: We conducted a parallel group randomized controlled trial of the CEaD intervention, comparing an online only version of the training (CEaD1) with the online version bolstered with in-person practice and feedback (CEaD2). Survey and interview data were collected from 1603 family decision makers and 273 requesters to assess the impact of both versions of the CEaD on requesters' communication skills and behaviors; the rate of family authorization to solid organ donation was obtained from administrative data provided by 9 organ procurement organizations. Results: Results revealed higher rates of authorization for requesters with less tenure (78% to 89%, P < 0.03) for both versions; however, CEaD1 also increased authorization rates for requesters with 3 or more years of experience (89% to 92%, P < 0.03). Both conditions resulted in an improvement in overall communication quality. Conclusions: We conclude that the CEaD was effective in improving requesters' communication skills, rates of family authorization to organ donation, and the overall quality of the donation experience.